Exploring the electrical and optical properties of silicon solar cell on thickness dependence by simulation approach - Yusof, Hany Nur Aqilah (2025)
In this final year project, the electrical and optical characteristics of solar cells are examined in relation to the thickness of the silicon substrate. Two simulation tools, PC1D for electrical analysis and PV Lighthouse for optical behavior, were used in the experiment. Tests were conducted on substrate thicknesses ranging from 30 μm to 190 μm, as well as surface texturing methods that used upright pyramid shapes to enhance light trapping. According to the PC1D simulations, thickness generally increased the value of key electrical parameters like overall efficiency, power output (Pmax), and short-circuit current (Isc). The highest efficiency was found at 190 μm (24.50%), however increases beyond 160 μm became less significant. Interestingly, the open- circuit voltage (Voc) stayed mostly stable, demonstrating that voltage performance is less influenced by thickness than current generation. In terms of optical performance, PV Lighthouse data showed that thicker substrates absorbed more light and reflected less, especially in the 300- 600 nm visible region. The introduction of upright pyramid surface textures improved absorption and enhanced simulated photocurrent density (Jg) by up to 50.62% compared to a non-textured, flat reference cell. These findings imply that adjusting substrate thickness, especially within the range of 160-190 μm, along with good surface texturing, can greatly improve solar cell performance without using unnecessary material. Overall, this research advances our understanding of how structural design decisions affect solar cell efficiency, and the findings can help guide the development of future silicon-based solar technologies that are more efficient, practical, and cost effective.